Agronomy and economics of two novel energy crops: Sida Hermaphrodita (L.) Rusby and Silphium Perfoilatum L. - Cumplido-Marin, Laura (Cranfield University, 2021)
The PhD project of title “Agronomy and Economics of two novel energy crops: Sida hermaphrodita (L.) Rusby and Silphium perfoliatum L.” was first conceptualised within the international project SidaTim. The main aim of the PhD was to reduce the uncertainty associated with the adoption of Sida hermaphrodita (L.) Rusby and Silphium perfoliatum L., through data gathering and evaluating their agronomic, economic and environmental performance. The main objectives of the PhD were: to review all available information and publications regarding the cultivation and energy production of the two species; to assess their agronomic performance in the UK; to examine the impact of their establishment on soil carbon; to determine their profitability against other potential crops across a European gradient; and to evaluate the greenhouse gas emissions associated with their cultivation. The novelty of the research lies on the establishment and assessment of two novel bioenergy crops in the UK compared across a range of climatic conditions, addressing the knowledge gaps regarding reliability and availability of information and assessment of their agronomic, economic and environmental performance. The first year of the project was dedicated to background research, collecting and processing the first set of soil analyses, producing all Silphium perfoliatum (L.) seedlings from seed, importing Sida hermaphrodita (L.) Rusby seeds from Germany, and in 2017 establishing an experimental site in Silsoe, Bedfordshire, UK. During the first three years,the mean maximum height of Sida hermaphrodita (L.) Rusby originated from seedlings was 198 cm and the maximum stem diameters were 14-18 mm. The mean maximum height of Silphium perfoliatum (L.) was 158 cm over three years and the maximum stem diameters were 14-16 mm. As opposed to the expected increase in maximum heights and diameters with time until plantation maturity, an overall reduction in maximum heights and diameters was recorded with time for Sida hermaphrodita (L.) Rusby, whilst only maximum diameters of Silphium perfoliatum (L.) decreased with time. Each year from February 2018, a winter harvest to measure the solid biomass production of Sida hermaphrodita (L.) Rusby and a summer harvest to measure the green biomass production of both Sida hermaphrodita (L.) Rusby and Silphium perfoliatum L. were carried out until September 2020. Mean dry biomass yields of Sida hermaphrodita (L.) Rusby plants grown from transplants for solid fuel for combustion were 1.7, 5.4, and 3.7 t DM ha⁻¹ in 2018, 2019, and 2020 respectively. Green biomass yields of Sida hermaphrodita (L.) Rusby for anaerobic digestion were on average 10.8, 8.1, 6.0 t DM ha⁻¹ in 2018, 2019, and 2020 respectively. The recorded declines in harvested biomass from Sida hermaphrodita (L.) Rusby are attributed to the combined effect of plant mortality, management and fertilisation practices. The corresponding mean green biomass yields of Silphium perfoliatum L. for anaerobic digestion were 4.6, 6.7, 8.9 t DM ha⁻¹ in 2018, 2019, and 2020. The second and third year focussed on objectives three and four, as well as collecting and processing the second set of soil analyses, data analysis, and writing up. The bulk density of the soil across 0-5 cm and 10-15 cm changed from 1.4-1.7 g cm³ prior to cultivation in 2017, to a uniform 1.4 g cm³ in 2020. The concentration of soil organic carbon at 0-5 cm decreased from 2.58% in 2017 to 1.85% in 2020, whereas at 10-15 cm, it increased from 1.86% to 2.12% over the three years. Overall, the mean soil organic carbon stocks (0-15 cm) declined from 65.0-67.6 t C ha⁻¹ in 2017 in 55.2-58.3 t C ha⁻¹ in 2020. The profitability of Sida hermaphrodita (L.) Rusby and Silphium perfoliatum (L.) was predicted over a rotation of 16 years and compared to that of an arable rotation and two other energy crops for the particular case of the UK and three other European countries. The calculated net present value (NPV) of Sida hermaphrodita (L.) Rusby was -1,591 £ ha⁻¹ without subsidies and 1,075 £ ha⁻¹ with subsidies; the corresponding net present values for Silphium perfoliatum (L.) were 3,031 £ ha⁻¹ and 5,607 £ ha⁻¹ . The study also calculated how much prices and costs would need to change for the NPV of the two crops to match the NPV of the most profitable energy crop or the arable rotation. Using an Excel model developed based on the IPCC guidelines, the greenhouse gas emissions for Sida hermaphrodita (L.) Rusby and Silphium perfoliatum (L.) production were calculated for a 16-year period. On a per annum basis, overall greenhouse gas emissions were estimated respectively at 4.2, 0.3, 2.2, -4.0 and -0.6 t CO2 eq ha⁻¹ for the arable rotation, short rotation coppice, Miscanthus, Sida hermaphrodita (L.) Rusby and Silphium perfoliatum (L.) systems. The environmental assessment demonstrated that cultivating Sida hermaphrodita (L.) Rusby and Silphium perfoliatum (L.) could potentially contribute to reducing greenhouse gas emissions.
Keywords: Bioenergy crops; soil carbon; biomass feedstock; crop economics; cost benefit analysis; greenhouse gas emissions